Auricular cartilage repair using cryogel scaffolds loaded with BMP‐7‐expressing primary chondrocytes. (26th December 2012) - Odabas, S.; Feichtinger, G. A.; Korkusuz, P.; Inci, I.; Bilgic, E.; Yar, A. S.; Cavusoglu, T.; Menevse, S.; Vargel, I.; Piskin, E.
Abstract The loss of cartilage tissue due to trauma, tumour surgery or congenital defects, such as microtia and anotia, is one of the major concerns in head and neck surgery. Recently tissue‐engineering approaches, including gene delivery, have been proposed for the regeneration of cartilage tissue. In this study, primary chondrocytes were genetically modified with plasmid‐encoding bone morphogenetic protein‐7 (BMP‐7) via the commercially available non‐viral Turbofect vector, with the aim of bringing ex vivo transfected chondrocytes to resynthesize BMP‐7 in vitro as they would in vivo. Genetically modified cells were implanted into gelatin–oxidized dextran scaffolds and cartilage tissue formation was investigated in 15 × 15 mm auricular cartilage defects in vivo in 48 New Zealand (NZ) white rabbits for 4 months. The results were evaluated via histology and early gene expression. Early gene expression results indicated a strong effect of exogenous BMP‐7 on matrix synthesis and chondrocyte growth. In addition, histological analysis results exhibited significantly better cartilage healing with BMP‐7‐modified (transfected) cells than in the non‐modified (non‐transfected) group and as well as the control. Copyright © 2012 John Wiley & Sons, Ltd.